Study on the Effect of Two Different Transfusion Methods in Neonates with Hyperbilirubinemia Induced by Non-Blood-Group Antibodies [Corrigendum] - Wu K (Dove Medical Press, 2021)
Wu K, Chen L, Huang H. Int J Gen Med. 2021;14:7311–7316. The authors have advised affiliations 1 and 2 and the correspondence address on page 7311 is incorrect. The text “Fujian Provincial Maternity and Children’s Hospital” should read “Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University”. The authors apologize for this oversight. Read the original article